Pembinaan Al-Quran Dalam Pembelajaran Tahsin Tilawah Pada Warga Binaan Lembaga Pemasyarakatan Perempuan (LPP) Kelas III Mataram - Hayati, Mardiyah; Hasanah, Niswatun; Yulianingsih, Yulianingsih; Urifah, Dewi (Lembaga Dongan Dosen, 2025)
The Women's Correctional Institution (LPP) Class III Mataram serves as a rehabilitation center for women from diverse social and economic backgrounds. The Qur'an Coaching Program through Tahsin Tilawah learning is designed to enhance the ability to read the Qur'an while supporting the understanding and appreciation of religious teachings. The methods used include varied teaching approaches supported by competent instructors, as well as evaluation of learning outcomes from 160 participants. The research results indicate that 90% of participants experienced a significant improvement in reading quality and tajwid application, while 70% felt more connected to their religious teachings. Additionally, the program positively impacted participants' mental and emotional health, boosting their self-confidence and social interactions. Despite the positive trends observed, the research also highlights challenges such as limited time and facilities that need to be addressed for the program's sustainability. Collaboration with religious institutions and the community is essential to enrich the learning material. Overall, this program is expected to contribute to the rehabilitation and social reintegration process, helping inmates return to society with better and more positive personalities.